Pathogenesis of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis With Severe Ocular Complications - Ueta, Mayumi (Frontiers in Medicine, 2021)
Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) is an acute inflammatory vesiculobullous reaction of the mucosa of the ocular surface, oral cavity, and genitals, and of the skin. Severe ocular complications (SOC) are observed in about half of SJS/TEN patients diagnosed by dermatologists and in burn units. Our investigation of the pathogenesis of SJS/TEN with SOC led us to suspect that abnormal innate mucosal immunity contributes to the ocular surface inflammation seen in SJS/TEN with SOC. We confirmed that cold medicines such as NSAIDs and multi-ingredient cold medications are the main causative drugs for SJS/TEN with SOC. Single nucleotide polymorphism (SNP) association analysis of cold medicine-related SJS/TEN with SOC showed that the Toll-like receptor 3 (TLR3)-, the prostaglandin-E receptor 3 (PTGER3)-, and the IKZF1 gene were significantly associated with SNPs and that these genes could regulate mucocutaneous inflammation including that of the ocular surface. We also examined the tear cytokines of SJS/TEN with SOC in the chronic stage and found that IL-8, IL-6, IFN-, RANTES, eotaxin, and MIP-1 were significantly upregulated in SJS/TEN with SOC in the chronic stage. Only IP-10 was significantly downregulated in SJS/TEN with SOC in the chronic stage. This mini-review summarizes the pathological mechanisms that we identified as underlying the development of SJS/TEN with SOC.